2018
DOI: 10.21037/atm.2018.06.31
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic assessment of moderate coronary lesions: a step towards complete revascularization in coronary artery bypass grafting

Abstract: Physiologic assessment of coronary lesions can effectively guide complete revascularization in patients undergoing CABG. Moreover, FFR/iFR-guided CABG was associated with significantly higher rates of three-vessel anastomoses, venous grafting, and graft distribution to the circumflex system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
0
12
0
3
Order By: Relevance
“…MACE was defined as a composite of death, myocardial infarction, or any revascularization by Moscona et al, 16 Fournier et al 18 and as composite of death, myocardial infarction, stroke, or any revascularization in the FARGO, FUTURE and GRAFFITI studies during the follow-up period. 13 - 19 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…MACE was defined as a composite of death, myocardial infarction, or any revascularization by Moscona et al, 16 Fournier et al 18 and as composite of death, myocardial infarction, stroke, or any revascularization in the FARGO, FUTURE and GRAFFITI studies during the follow-up period. 13 - 19 …”
Section: Methodsmentioning
confidence: 99%
“…Os desfechos estudados foram: morte por todas as causas, infarto do miocárdio (IM), revascularização do vaso alvo (TVR) e eventos cardiovasculares adversos maiores (MACE) durante o período de acompanhamento. MACE foi definido como um composto de morte, infarto do miocárdio ou qualquer revascularização de Moscona et al, 16 Fournier et al; 18 e como um composto de morte, infarto do miocárdio, derrame ou qualquer revascularização dos estudos FARGO, FUTURE e GRAFFITI durante o período de acompanhamento. [13][14][15][16][17][18][19] Análise estatística Para calcular as estimativas do efeito agrupado, utilizamos a variância inversa assumindo um modelo de efeito fixo, e o método de DerSimonian e Lard 21 assumindo o modelo do efeito randômico.…”
Section: Desfechosunclassified
See 2 more Smart Citations
“…Prior to patients undergoing CABG, an accurate diagnostic assessment of the extent of the optimal CAD targets must be made, often approached only using anatomic visualization strategies. The article "Physiologic assessment of moderate coronary lesions: a step towards complete revascularization in coronary artery bypass grafting", by Moscona et al present a method utilizing the physiologic assessment of coronary lesions to effectively guide the complete revascularization in patients undergoing CABG (13). Through a retrospective review of medical records from patients at Tulane Medical Center, Moscona et al via calculation of the fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR) found that FFR/iFR-guided CABG was associated with higher rates of successful three-vessel anastomoses, venous grafting and graft distribution to the circumflex system.…”
mentioning
confidence: 99%